Fulbright Scholarship Award ( Visiting Scholar program, MIT CSAIL) - Ioannou, Andri (My University, 2026)
Cypriot academics with The Fulbright Program Visiting Scholar program spend an academic semester in the 🇺🇸, engaging in research or teaching. In fall2-24 Andri Ioannou worked with the MIT CSAIL HCI Engineering group at Massachusetts Institute of Technology (MIT), USA. The Fulbright Award, Visiting Scholar program, is a very prestige award.
Keywords: Education